Social relationships and grit in English as a foreign language learning among high school students: A three-wave longitudinal study - Tianxue Cui; Yanchao Yang; Yanchao Yang (Frontiers in Psychology, 2022)
This study examined the longitudinal reciprocal relations between students’ grit and their perceptions of social relationships (teacher-student and peer relationships) in studying English as a foreign language (EFL). A total of 2,435 students from Grades 10-11 in China (Mage = 16.40 years old, 54.2% female) participated in the study on three occasions across 1 year. The three-wave cross-lagged analytic model results indicated that (a) peer relationship and grit reciprocally enhanced each other across both intervals; (b) the teacher-student relationship at Time 2 was influenced by Time 1 grit, but not vice versa. Nevertheless, the teacher-student relationship transactionally facilitated each other during the second interval (from Time 2 to Time 3). The multiple-group confirmatory factor analysis (MG-CFA) results indicated that such relations remained stable across gender. The study’s findings contribute to ongoing research delineating the dynamic system between social relationships and grit in EFL learning. It also reveals that males and females benefit similarly during social communications with peers and their English language teachers. Implications for educational practices were discussed.